2002
DOI: 10.4049/jimmunol.169.11.6324
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF Transgene-Based Adjuvant Allows the Establishment of Protective Mucosal Immunity Following Vaccination with Inactivated Chlamydia trachomatis

Abstract: Cellular and humoral immune responses induced following murine Chlamydia trachomatis infection confer almost sterile protection against homologous reinfection. On the other hand, immunization with inactivated organism induces little protective immunity in this model system. The underlying mechanism(s) that determines such divergent outcome remains unclear, but elucidating the mechanism will probably be important for chlamydial vaccine development. One of the distinct differences between the two forms of immuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 53 publications
1
50
0
1
Order By: Relevance
“…delivery of a rBCG strain secreting detectable levels of GM-CSF in situ augments local immunogenicity and demonstrates significant protection against M. tuberculosis infection. GM-CSF is critical to the differentiation of myeloid cells such as DC and macrophages from haematopoietic stem cell precursors, yet in the lung it has been shown to possess unique functions in the regulation of inflammation and host defense against infectious pathogens, as well as pulmonary surfactant and alveolar cell homeostasis [23][24][25][26]. The pattern of GM-CSF production within the lung, with GM-CSF concentrations diminishing over time (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…delivery of a rBCG strain secreting detectable levels of GM-CSF in situ augments local immunogenicity and demonstrates significant protection against M. tuberculosis infection. GM-CSF is critical to the differentiation of myeloid cells such as DC and macrophages from haematopoietic stem cell precursors, yet in the lung it has been shown to possess unique functions in the regulation of inflammation and host defense against infectious pathogens, as well as pulmonary surfactant and alveolar cell homeostasis [23][24][25][26]. The pattern of GM-CSF production within the lung, with GM-CSF concentrations diminishing over time (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…muridarum strain Nigg was grown in HeLa 229 cells in Eagle's minimal essential medium (Invitrogen Life Technologies) supplemented with 10% FCS. Elementary bodies (EBs) were purified from HeLa cells on discontinuous density gradients of Renografin-76 (Squibb Canada) as described previously (13).…”
Section: Chlamydiamentioning
confidence: 99%
“…Su et al (12) previously demonstrated that DCs pulsed ex vivo with Chlamydia protected mice against chlamydial infection. Our previous work has demonstrated that expression of GM-CSF (a cytokine known to mobilize DCs) in the mouse airway significantly enhanced systemic Th1 cellular immune responses following mucosal immunization with inactivated Chlamydia muridarum (13). Subsequent in vitro observations demonstrated that DCs exposed to live or to UV-irradiated C. muridarum develop distinct phenotypes, such that DCs exposed to live Chlamydia become mature and effectively present Ag to Chlamydia-specific CD4 T cells, while DCs exposed to UV-irradiated Chlamydia were less immunologically mature (14).…”
mentioning
confidence: 99%
“…Moreover, it has been shown recently that recombinant BCG expressing GM-CSF is highly efficient in preventing TB in a mouse model [41], inducing a similar cytokine response that we observed when AdGM-CSF was administered 1 day before infection. In fact, administration of GM-CSF, or inducing its expression, has been useful in the treatment against other pulmonary infections such as aspergillosis [43], Chlamydia trachomatis [44] and pneumococcal pneumonia [45]. Moreover, the delivery of recombinant human GM-CSF by inhalation was shown to be beneficial in the treatment of alveolar proteinosis and it was well tolerated in healthy subjects [46].…”
Section: Discussionmentioning
confidence: 99%